"The persistence of memory"—Hermaphroditism in nematodes. Issue 2 (30th June 2016) - Ellis, Ronald E
SUMMARY: Self‐fertility has evolved many times in nematodes. This transition often produces an androdioecious species, with XX hermaphrodites and XO males. Although these hermaphrodites resemble females in most respects, early germ cells differentiate as sperm, and late ones as oocytes. The sperm then receive an activation signal, populate the spermathecae, and are stored for later use in self‐fertilization. These traits are controlled by complex modifications to the sex‐determination and sperm activation pathways, which have arisen independently during the evolution of each hermaphroditic species. This transformation in reproductive strategy then promotes other major changes in the development, evolution, and population structure of these animals. Mol. Reprod. Dev. 84: 144–157, 2017. © 2016 Wiley Periodicals, Inc .